2020
DOI: 10.26418/ja.v1i1.41654
|View full text |Cite
|
Sign up to set email alerts
|

Hambatan Epistemologi Pemahaman Konseptual Berdasarkan Taksonomi Solo Siswa

Abstract: This study aims to explain and describe the epistemological obstacle of students' mathematical conceptual understanding based on the SOLO taxonomy at MTs Negeri 2 Pontianak. This research uses a descriptive qualitative method with a survey form. The subjects of this research is 35 students in class VIII F MTs Negeri 2 Pontianak. Data collection techniques that used were test and and non-test. Data collection tools that used were conceptual understanding tests and interview. The results of data analysis from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…In this study, the authors found that the majority of students scored below the minimum completion criteria, and the majority of students lacked understanding of probability material, lacked mastery of the questions, miscalculated, and were less careful in working on problems marked by errors made by students when working on probability story problems. From these student errors, obstacles arise when learning, known as learning obstacles (Utami et al, 2020;Hikmah, 2021). It means that students experience learning obstacles in solving probability story problems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors found that the majority of students scored below the minimum completion criteria, and the majority of students lacked understanding of probability material, lacked mastery of the questions, miscalculated, and were less careful in working on problems marked by errors made by students when working on probability story problems. From these student errors, obstacles arise when learning, known as learning obstacles (Utami et al, 2020;Hikmah, 2021). It means that students experience learning obstacles in solving probability story problems.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian terdahulu menunjukkan bahwa pada pembelajaran matematika siswa masih mengalami epistemological obstacle pada indikator pemahaman konseptual matematis, yang diakibatkan karena siswa belum memahami konsep dasar materi yang sedang dipelajarinya (Utami et al, 2020). Fakta yang diperoleh dari hasil wawancara di lapangan dengan guru matematika di SMA Negeri 7 Tasikmalaya menunjukkan bahwa siswa masih menghadapi kesulitan dalam belajar matematika dalam menyelesaikan berbagai jenis persoalan yang beragam, terutama pada soal-soal yang disajikan dalam bentuk cerita atau non-rutin.…”
Section: Pendahuluanunclassified
“…Menurut Rosmawati (dalam Pranata, 2016: 34) pemahaman konsep adalah yang berupa penguasaan sejumlah materi pembelajaran, dimana siswa tidak sekedar mengenal dan mengetahui, tetapi mampu mengungkapkan kembali konsep dalam bentuk yang lebih mudah dimengerti serta mampu mengaplikasikannya (Utami et al, 2020). Pengertian pemahaman menurut Sudjana (2005:50) Pemahaman memerlukan kemampuan menangkap makna atau makna suatu konsep, hal ini memerlukan hubungan atau keterkaitan antara konsep dengan makna yang terkandung dalam konsep tersebut.…”
Section: Pendahuluanunclassified